2010
DOI: 10.1007/s00779-009-0267-y
|View full text |Cite
|
Sign up to set email alerts
|

Space and places: when interacting with and in physical space becomes a meaningful experience

Abstract: Human experience of physical space and places is a complex phenomenon that includes geographical and sensorial, as well as more social and interpersonal dimensions. We investigate theoretical insights from computing research and environmental psychology on space and place to determine the different dimensions of the experience of physical space. Empirical results from a case study on creative activities for environment exploration are also presented. We indicate five dimensions that encompass the different way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 32 publications
(53 reference statements)
2
56
0
2
Order By: Relevance
“…As such, our game provides an invitation to play and a convenient alibi for behaviour that challenges the social norm of these spaces. 1 Activity Village -http://www.activityvillage.co.uk/ We hope that by engaging visitors through play that we can give these places personal meaning or what Harrison and Dourish [6] describe as a sense of place (discussed [10]). A positive sense of place can mean different things to different places, for example, in a library it might mean we visit and borrow books more often and in the case of a heritage site it means we can change visitor's attitudes so they can become future custodians of these spaces.…”
Section: Next Stepsmentioning
confidence: 99%
“…As such, our game provides an invitation to play and a convenient alibi for behaviour that challenges the social norm of these spaces. 1 Activity Village -http://www.activityvillage.co.uk/ We hope that by engaging visitors through play that we can give these places personal meaning or what Harrison and Dourish [6] describe as a sense of place (discussed [10]). A positive sense of place can mean different things to different places, for example, in a library it might mean we visit and borrow books more often and in the case of a heritage site it means we can change visitor's attitudes so they can become future custodians of these spaces.…”
Section: Next Stepsmentioning
confidence: 99%
“…Lentini et al indicated five dimensions that encompass human experiences in physical space and place: Geometrical and Geographical, Sensorial , Cultural, Personal, and Relational [7]. The first three dimensions represent aspects of place and space, and the latter two dimensions address emotional aspects.…”
Section: B Related Workmentioning
confidence: 99%
“…In this regard researchers have stressed the need to investigate further situated, embodied everyday practices and the interrelationship between space, place and technology [17,22]. For example, [2,35] highlight how political notions of sustainability must be understood in connection to the felt experiences and social practices in physical environments.…”
Section: Introductionmentioning
confidence: 99%